2012
DOI: 10.3767/003158512x652633
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Planet description sheets: 107–127

Abstract: Novel species of microfungi described in the present study include the following from Australia: Phytophthora amnicola from still water, Gnomoniopsis smithogilvyi from Castanea sp., Pseudoplagiostoma corymbiae from Corymbia sp., Diaporthe eucalyptorum from Eucalyptus sp., Sporisorium andrewmitchellii from Enneapogon aff. lindleyanus, Myrmecridium banksiae from Banksia, and Pilidiella wangiensis from Eucalyptus sp. Several species are also described from South Africa, namely: Gondwanamyces wingfieldii from Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
248
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(261 citation statements)
references
References 45 publications
12
248
1
Order By: Relevance
“…Likewise P. amnicola is known only from Australia where it was found in river and soil beneath a diseased Patersonia spp. plant (Crous et al 2012). There is no evidence to suggest that P. amnicola and P. thermophila were introduced into South Africa.…”
Section: Figmentioning
confidence: 90%
See 2 more Smart Citations
“…Likewise P. amnicola is known only from Australia where it was found in river and soil beneath a diseased Patersonia spp. plant (Crous et al 2012). There is no evidence to suggest that P. amnicola and P. thermophila were introduced into South Africa.…”
Section: Figmentioning
confidence: 90%
“…Likewise P. bilorbang (Phytophthora taxon OakSoil) is well known from France Delatour 1999, Brasier et al 2003), North America (Reeser et al 2011) and Australia (Aghighi et al 2012). In Australia several other species, such as P. amnicola, P. fluvialis, P. inundata and P. thermophile, were isolated frequently from water , Crous et al 2012, Hü berli et al 2013. Given their wide distribution elsewhere, perhaps some of these species occur in South Africa but the limited geographic area sampled in the present study was insufficient to test this.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Chrysocrypta Crous & Summerell Crous et al (2012c) introduced this monotypic, coelomycetous genus. listed Chrysocrypta under Cryphonectriaceae.…”
Section: Catenulomyces Egidi and De Hoogmentioning
confidence: 99%
“…Phookamsak et al (2014) agreed with this familial placement. Crous Crous et al (2012c) Xerombrophila Baral Baral et al (2013) introduced this genus with hyphomycetous asexual morph. DNA sequence analyses showed that it belongs to Helotiaceae.…”
Section: Catenulomyces Egidi and De Hoogmentioning
confidence: 99%